Core competencies required of project managers - Michael Birkhead; Margaret Sutherland; Tudor Maxwell (South African Journal of Business Management, 2000)
Project management is internationally recognised as a management tool that is critical for success in the current work environment. In South Africa, initiatives are under way to produce internationally acceptable education and certification standards for the profession. The aim of this study is to identify the competencies and training needs required of project managers operating in South Africa's unique context. A questionnaire based on both previous international studies and personal interviews was administered by e-mail to members of the Project Management Institute of South Africa. Data was received from 128 respondents operating primarily in information technology, construction and engineering fields across the country. The results of the survey establish a rank ordered list of the competencies and training needs of South African project managers, and confirm that project management competencies are generic in nature. The findings are unique to South Africa, and proffer a set of core competencies which has important implications for the certification and training of South African project managers.
Keywords: 650